Environmental Standards in a Large Open Economy - Petchey, Jeffrey (2015)
The small-country price-taking assumption of Oates and Schwab is relaxed to consider a large open economy that can influence its net capital return. This creates an incentive for the country to distort its policies. The key question asked is whether this induces inefficient outcomes. The result is that if the country has a dedicated tax on capital and uses this tax optimally, the Oates and Schwab first-best result still holds. However, efficiency in a large open economy requires that the tax on capital be nonzero, unlike Oates and Schwab where the capital tax must be zero for first-best efficiency.